KEWAJIBAN ADVOKAT MEMBERI BANTUAN HUKUM PRODEO BAGI WARGA MISKIN - Tina Permata Sari (Jurnal Jendela Hukum, 2025)
The obligation of advocates to provide free legal assistance (prodeo) is a crucial instrument to ensure the principle of access to justice for the poor. Although normatively regulated in Article 22 of Law Number 18 of 2003 on Advocates and reinforced by Law Number 16 of 2011 on Legal Aid, its implementation has yet to reflect substantive justice. The legal issue addressed in this study lies in the gap between ideal legal norms and practical realities, where prodeo legal assistance remains ineffective due to weak professional commitment, limited institutional support, and low legal literacy among the poor. This study aims to analyze the legal basis of advocates' obligation to provide prodeo legal aid, evaluate its practical implementation, and propose solutions to the challenges encountered. This research uses a normative-empirical legal method. The results show that the implementation of the prodeo obligation still faces structural and cultural obstacles, such as lack of oversight, underperformance of professional organizations, uneven distribution of legal aid institutions, and insufficient awareness among advocates and the public regarding the right to legal aid. To overcome these issues, it is necessary to strengthen regulations, provide appropriate incentives, enhance the capacity of legal aid institutions, and expand public legal education. These efforts represent not only a normative legal obligation but also a constitutional and moral responsibility to realize justice that is inclusive and accessible to all citizens.